2006
DOI: 10.1063/1.2335376
|View full text |Cite
|
Sign up to set email alerts
|

Study on liquid-liquid transition of chlorinated butyl rubber by positron annihilation lifetime spectroscopy

Abstract: The existence of liquid-liquid transition (Tll) above the glass transition (Tg) in amorphous polymers remains a controversial topic. In this letter, positron annihilation lifetime spectroscopy was used to detect Tll in cured and uncured chlorinated butyl rubber. It is found that the temperature spectra of orthopositronium lifetime and free-volume fraction of both samples clearly demonstrate two inflection points around −70 and −10°C, corresponding to Tg and Tll, respectively, while the orthopositronium intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…While the above considerations show that a quantitative description of dielectric and, at least, a qualitative account for PALS data is possible within the TOP model, one has to state that this approach relates to the structural relaxation and does not explain the observation of at least two distinct regions in the increasing part of s 3 ðTÞ separated by T L b1 , as observed in some glass-formers [10][11][12][13]17]. In section 4.1, based on a comparison with temperaturedependent dielectric loss data at x % 1=s 3 , we have argued that the anomaly at T L b1 could be related to the transition from a-relaxation to EW dominated behavior.…”
Section: Common Discussion Of the Phenomenological And Model Analyzesmentioning
confidence: 95%
See 3 more Smart Citations
“…While the above considerations show that a quantitative description of dielectric and, at least, a qualitative account for PALS data is possible within the TOP model, one has to state that this approach relates to the structural relaxation and does not explain the observation of at least two distinct regions in the increasing part of s 3 ðTÞ separated by T L b1 , as observed in some glass-formers [10][11][12][13]17]. In section 4.1, based on a comparison with temperaturedependent dielectric loss data at x % 1=s 3 , we have argued that the anomaly at T L b1 could be related to the transition from a-relaxation to EW dominated behavior.…”
Section: Common Discussion Of the Phenomenological And Model Analyzesmentioning
confidence: 95%
“…Moreover, at T L b2 , s 3 is often close to the mean relaxation time of the primary a process, s a ðT L b2 Þ, as obtained from a standard peak analysis [10,13,16,17]. Often, a slighter change of slope at T L b1 , closer to the glass transition temperature T PALS g is observed [7][8][9][10][11][12][13] as was sometimes quantified by the best linear fitting [10][11][12][13]. Similarly as for T L b2 , it is found that T L b1 is related to the temperature T a (À6), at which the mean a -relaxation time from DS s a ðT L b1 Þ reaches a value of 10 À6 ± 1 s [10,13].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Phenomenological analysis revealed the existence of several characteristic PALS temperatures in the liquid state marked according to a unified notation [9] as T PALS g , T L b1 and T L b2 ¼ T r [7] = T e [8], the two latter being located at T L b1 $ 1.2-1.4 T PALS g [9][10][11] or T L b2 $ 1.4-1.7 T PALS g [7][8][9], respectively. Evidently, the full utilization of PALS method for the structuraldynamic characterization of any disordered system requires understanding of the physical significance of these PALS temperatures.…”
Section: Introductionmentioning
confidence: 99%